The impact of financial technology on commercial banks: Evidence from China - Tian Xiang, Zhou (2023)
Financial technology (i.e., FinTech) employs advanced scientific and technological tools to create innovative products and services for financial institutions. However, the rapid advancements in FinTech have affected traditional banks' operations. This study aimed to investigate the impact of FinTech on impact on commercial banks in China. Drawing on previous literature and empirical evidence, annual financial data was collected from 23 local commercial banks in China covering the period from 2011 to 2020. The data was analyzed using a dynamic panel data model (i.e., GMM). The findings suggest that FinTech has an overall positive impact on the return on assets of commercial banks. However, this impact varies across different types of commercial banks, with city commercial banks being the least affected, followed by joint-stock commercial banks and large state-owned commercial banks. Keywords: FinTech, commercial bank, financial technology, Chinese banks